Exploring the potential impact of empiric antibiotic de-escalation for suspected early onset neonatal sepsis - Ain Ibrahim, Nazedah; Makmor Bakry, Mohd; Ishak, Shareena; Mohd Tahir, Nurul Ain; Mohamed Shah, Noraida (The Journal of Infection in Developing Countries, 2025)
Introduction: The aim of this study was to explore the impact of empiric antibiotic de-escalation for suspected early onset neonatal sepsis (EONS) on clinical and economic outcomes. This was a multicenter prospective cohort study. Newborns were recruited from 3 neonatal intensive care units (NICUs) in Klang Valley, Malaysia. Methodology: All newborns in the NICU, and prescribed with empiric antibiotics within 72 hours for EONS over 4 months were included. Data on newborns’ characteristics, clinical outcomes, cost-effectiveness in 7 days, and mortality in 28 days were recorded. Antibiotic usage was divided into de-escalation and non-de-escalation groups, with 1:1 data matching for gestational age (weeks) and birth weight (± 0.1 kg). Time to treatment success, 28-days all-cause mortality, and cost-effectiveness were analyzed. Results: A total of 687 newborns were included. Data matching was conducted for grouping into de-escalation and non-de-escalation groups (n = 262 per group) for comparative analysis. There was no significant difference in the treatment failure rate (p = 0.742) and all-cause mortality in 28-days of life (p = 0.052) between the groups. However, a significant difference in terms of time to treatment success (median 3 days in the de-escalation group vs. 5 days in the non-de-escalation group; p < 0.001)) was observed. Cost-effectiveness analysis showed cost-saving of USD 47.80 per newborn per day for the de-escalation group. Conclusions: Early empiric antibiotic de-escalation should be considered in all newborns with a low risk of EONS. This practice did not increase the treatment failure rate and provided a beneficial outcome.